Supporting early academic family medicine careers with the clinician scholar enhanced-skills program (Canadian Medical Education Journal, 2019)
Context:The Clinician Scholar Program (CSP) is an enhanced-skills (R3) residency program to train clinician researchers/educators/leaders for academic family practice. This article intends to share Laval University’s CSP development and evaluation strategy, and provide recommendations for similar innovations in other disciplines/settings.MethodsThis article uses Kern’s model to present the program development, and a program-oriented approach for program evaluation, carried from 2011 to 2017 using descriptive data. Questionnaires, reflexive texts and an Objective Structured Teaching Exam supported data collection.Results7 CSP graduates and 14 controls participated in the program evaluation. Residents were highly satisfied with the program, nevertheless suggested allowing training later in career. The CSP enriched knowledge, skills and attitudes about academic practice. CSP increased residents’ entrustment level about academic competencies. All graduates joined an academic practice within five years of program completion.ConclusionsKey recommendations to implement similar programs include academic medicine core training, project-based learning with learner-centered objectives, relevant and authentic learning and assessment, and multi-level program evaluation approach. Programs should consider concomitant graduate studies and opportunity to offer such training after a few years of clinical practice to meet other needs at a timely stage of career.